Research and Application of a New Type of Substation Transportation Inspection Simulation Training System. Issue 4 (March 2021) - Wang, Meikun; Gao, Feng; Shi, Jiaoyang; Zheng, Wensu; Zhao, Xilan; Wang, Tuo
Abstract: For the shortcomings of the existing professional training for substation operation inspection, this paper proposes a design of a new type of substation operation inspection simulation training system based on networking, adaptive learning, gamification and other technologies. The system solves the problem that substation operators lack modern training tools and cannot carry out networked simulation learning, and conduct targeted and personalized learning based on user knowledge and skills. The system lacks guidance and evaluation functions in the learning process, and the system lacks interest and cannot effectively stimulate learners' interest in learning and other issues. The research results of this article have been successfully applied in the Gansu Electric Power Company and have obtained good training effects.